2016
DOI: 10.1038/srep24014
|View full text |Cite|
|
Sign up to set email alerts
|

Somatic Mutations and Genetic Variants of NOTCH1 in Head and Neck Squamous Cell Carcinoma Occurrence and Development

Abstract: A number of genetic variants have been associated with cancer occurrence, however it may be the acquired somatic mutations (SMs) that drive cancer development. This study investigates the potential SMs and related genetic variants associated with the occurrence and development of head and neck squamous cell carcinoma (HNSCC). We identified several SMs in NOTCH1 from whole-exome sequencing and validated them in a 13-year cohort of 128 HNSCC patients using a high-resolution melting analysis and resequencing. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…When associated with Notch proteins, RBPJ acts as a transcriptional activator, but when not associated with Notch proteins, it exists in complexes with corepressors and serves to block transcription . Even though there are no studies that link RBPJ activity to laryngeal carcinoma, in 2016, Liu et al found that somatic mutations in NOTCH1 correlated strongly with higher rates of recurrence and lower survival in HNSCC. It is likely that genes that regulate Notch signalling, such as RBPJ , are in some way responsible for altering HNSCC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…When associated with Notch proteins, RBPJ acts as a transcriptional activator, but when not associated with Notch proteins, it exists in complexes with corepressors and serves to block transcription . Even though there are no studies that link RBPJ activity to laryngeal carcinoma, in 2016, Liu et al found that somatic mutations in NOTCH1 correlated strongly with higher rates of recurrence and lower survival in HNSCC. It is likely that genes that regulate Notch signalling, such as RBPJ , are in some way responsible for altering HNSCC prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although this SNP did not cause amino acid changes, it was located in EGF-like domains of the NOTCH1 extracellular region that may play a dual role in tumorigenesis to regulate various oncogenes and tumor suppressor genes. Both overexpression and downregulation of NOTCH and ligands have been implicated in several human cancers (23)(24)(25)(26). Somatic mutations of NOTCH1 have been suggested to play an oncogenic role in breast, colorectal, and pancreatic cancers (27)(28)(29)(30).…”
Section: Discussionmentioning
confidence: 99%
“…Our patient's tumor also had a functional loss of NOTCH1 . Somatic mutations in NOTCH1 have been reported in 10–15% of head and neck squamous cell carcinomas . The majority of NOTCH pathway alterations are activating mutations and a smaller subset are inactivating.…”
Section: Discussionmentioning
confidence: 99%